Special issue who belongs? : immigration, citizenship, and the constitution of legality - Sarat, Austin (Emerald, 2012)
The objective of "Studies in Law, Politics, and Society" is to provide a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. Whereas other law related publications publish within a single domain - the humanities, social science, or legal doctrine. Studies seeks to bridge those divides. We encourage submissions from a broad range of legal scholars and welcome articles exemplifying different theoretical perspectives and methodological approaches. We welcome submissions from an international group of scholars.
Keywords: Law -- Emigration & Immigration.; Political Science -- Political Freedom & Security -- Human Rights.; Law -- General.; Citizenship & nationality law.; Immigration law.; Citizenship.; Emigration and immigration -- Government policy.; Emigration and immigration law.; elektronické knihy; electronic books